Revolutionary Advances: Exploring the Applications of 3D Printing in Dentistry (Academia Journal of Medicine, 2023)
3D printing technology has emerged as a  transformative force in the field of dentistry, offering  unprecedented advancements in precision,  customization, and patient care. This evidence-based  article explores the impact of 3D printing in dentistry,  supported by recent studies and research. The  utilization of 3D printing has led to superior precision  in the fabrication of dental prosthetics, customized  patient-specific care, and improved surgical planning  through the creation of guides. Furthermore,  advancements in material science have ensured the  biocompatibility and durability of 3D printed dental  materials. While promising, challenges such as  regulatory standards, material safety, and cost effectiveness warrant consideration. The evidence  presented underscores the potential of 3D printing  to revolutionize the field of dentistry, offering a  glimpse into a future defined by personalized,  efficient, and effective dental treatments.
Keywords: 3D printing; Dentistry; Dental materials